1996
DOI: 10.1111/j.1524-4725.1996.tb00337.x
|View full text |Cite
|
Sign up to set email alerts
|

Duplex Ultrasound Examination of the Acutely Painful and Swollen Leg

Abstract: The variety of pathological processes related to the lower limb veins and the extravascular tissue suggest that routine, "detailed" ultrasound scanning would be indicated in all acutely symptomatic legs with a suspected venous disorder. The important diagnostic information so gained provides guidance to the most appropriate treatment strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2000
2000
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
0
4
0
1
Order By: Relevance
“…It may also be a decisive factor in the presence of clinically difficult differential diagnosis with cellulitis, panniculitis, erythema nodosum, insect bites, and lymphangiitis. 12,19,[47][48][49]…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…It may also be a decisive factor in the presence of clinically difficult differential diagnosis with cellulitis, panniculitis, erythema nodosum, insect bites, and lymphangiitis. 12,19,[47][48][49]…”
Section: Diagnosismentioning
confidence: 99%
“…A renewed interest for this disease has arisen in the last decade by the evidence for a significant and previously unsuspected association with deep vein thrombosis (DVT) and pulmonary embolism (PE), which often are clinically occult. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] Recent studies have shown the risk of venous thromboembolic complications in patients with isolated SVT by the direct propagation of superficial thrombosis to the deep vein system or the development of DVT in noncontiguous sites with a subsequent real risk of PE. 13,15,[19][20][21] These data have challenged the traditional belief that SVT is always a benign and trivial disease, and have encouraged new clinical research in this field.…”
mentioning
confidence: 99%
“…Complete US needed to be repeated in only very few patients (1.4%) because of inadequate tests. study (27) evaluating 106 limbs without venous thrombosis, the most frequent ultrasound findings were incompetent leg veins or soft tissue masses (Baker's cyst and calf hematoma).…”
Section: Discussionmentioning
confidence: 99%
“…Extension of superficial thrombophlebitis to the deep venous system occurs through the proximal long and short saphenous veins to the common femoral and popliteal veins, respectively, and through the perforating veins. [3][4][5]8,13 The use of duplex scanning for diagnosis is controversial. Some argue that it should be performed to establish the diagnosis and to evaluate the deep venous system with a follow-up scan to assess resolution of the condition and the status of the deep veins.…”
Section: Definition and Diagnosismentioning
confidence: 99%